The use of a starch-based superabsorbent polymer to support and optimise potato production in the sandy soils of the Sandveld production region in South Africa. - Smit, Lome (Stellenbosch : Stellenbosch University, 2023)
Thesis (MScAgric)--Stellenbosch University, 2023.